The effects of Flaxlic block supplementation on finishing feedlot heifers - Quinn, M.J.; Loe, E.R.; Webb, A.S.; Corrigan, M.E.; Drouillard, James S.; Depenbusch, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine the effects of FlaxLic supplement blocks, fed free-choice during feedlot finishing, on heifer performance, carcass quality, and fatty acid profiles of loin steaks. Heifers (n=302, 1059±7 lb initial bodyweight) were fed diets based on steam-flaked corn. Cattle were assigned to dirt surfaced pens (12 to 13 heifers/pen, 12 pens/treatment). Treatments consisted of control (no block) or FlaxLic free-choice block supplements. Loins were obtained from three animals randomly selected from each pen for measurement of fatty acid profiles. Average daily gain and feed:gain were not different over the 75-day feeding trial. Dry matter intake was less for heifers supplemented with FlaxLic blocks. There were no differences between treatments for carcass characteristics. Heifers supplemented with FlaxLic blocks had greater concentrations of 18:3n3 (alpha-linolenic acid) fatty acids in loin steaks, compared with controls. The ratio of omega-6:omega-3 fatty acids was also reduced by supplementation with FlaxLic blocks.
Keywords: Beef; Flaxlic; Finishing heifers